FORMATION OF READINESS OF FUTURE READERS TO PATRIOTIC EDUCATION OF CHILDREN OF THE SENIOR PRESCHOOL AGE: PEDAGOGICAL MODEL - Filimonova, Tatiana (Educological discourse, 2018)
The article highlights the main provisions of the model of forming the future teacher's readiness for the patriotic education of children of senior preschool age. The definitions of the concept «model» in the scientific and pedagogical literature are presented. It is noted that the use of modeling allows to harmonize the formal-logical and informative approach in the course of pedagogical research and analysis of its results. The constituent modules of the developed model are characterized: goal, principles, functions, pedagogical conditions, stages of preparation, components and criteria, levels and results. The urgency of patriotic education is conditioned by the process of forming a united political nation in Ukraine, and patriotic education of youth today is one of the main priorities of the humanitarian policy in Ukraine, an important component of the national security of Ukraine. Therefore, the problem of students' readiness for patriotic education in pre-school educational institutions is more urgent than ever. The construction and maintenance of the model of forming the readiness of the future educator for the patriotic upbringing of children of the senior preschool age involves taking into account the current trends in the reform of the educational system of Ukraine, namely: a substantial change in the requirements for organizing the process of training future teachers for educational activities, organizing the educational process from the standpoint of a person , activity and competency approaches.